Connection of boxers' combat styles with psycho-physiological characteristics - G.V. Korobeynikov; V.V. Aksutin; I.I. Smoliar (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: By dominating physical characteristics boxers' combat styles are divided into "strongmen", "paced in hold" and "players". However, connection of combat style with psycho-physiological characteristics of elite boxers has been remained not determined. Material: in the research 28 elite sportsmen (master of sports and international masters of sports) participated. Psycho-physiological characteristics were studied with the help of hardware and software psycho-diagnostic complex "Multi-psycho-meter 05". Results: it was found that attacking combat style is accompanied by presence of high workability, reduced tiredness and anxiety, presence of psychological comfort. It was also found that defensive combat style is characterized by better quickness and processing of information. It happens at the account of worsening of qualitative characteristics: efficiency and effectiveness. We also detected presence of more rigid organization of psycho-physiological status of boxers, having attacking combat style (strongmen) in comparison with boxers of defensive style (players and paced in hold).